2016
DOI: 10.1016/j.applthermaleng.2015.09.057
|View full text |Cite
|
Sign up to set email alerts
|

A heat transfer correlation for transient vapor uptake of powdered adsorbent embedded onto the fins of heat exchangers

Abstract: Highlights Detailed study on transient heat transfer of an adsorbent coated heat exchanger. Adsorbent-adsorbate interaction contributes 75% of the total thermal resistance. Transient local heat transfer deviates from the overall value due to thermal mass. A correlation for the transient local adsorption heat transfer coefficient. ABSTRACTWe present a detailed study on the transient heat transfer phenomena of powdered-adsorbent mixed with an organic binder for adherence to the fins of a heat exchangers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, for the equivalent powdered bed, the λ ads = 0.11 W/m K and AQSOA binder-based coating λ ads = 0.36 W/m K 126 ; for zeolites, zeo-types, and silica gel, λ ads in the range 0.10–0.20 W/m K. 26,32,120 Restuccia et al 26 identified a binder-based coating with λ ads = 0.30 W/m K. λ ads values for condensed beds and specifically synthesized coatings were nearly two orders of magnitude higher than for binder-based coatings and loose grains/pellets. For loose grains, the values for convective heat transfer coefficients ( h ads ) are reported in the range of 70–120 W/m K, 133 but the most commonly used values are 10–50 W/m K. 133 For the other configurations, the convective heat transfer coefficients are greater than 1000 W/m K, such as, for directly synthesized SAPO-34 coatings on aluminum fibers, binder-based coating of silica gel, and consolidated 13X zeolite, the h ads are >1000 W/m K 125 for former, and up to 3000 W/m K 125,134 for the later ones, respectively. Such findings are helpful for improved interaction among the AHEx metal and adsorbent surface while consolidated beds or coatings are used rather than loose grains.…”
Section: Design and Operation Of Ahpsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for the equivalent powdered bed, the λ ads = 0.11 W/m K and AQSOA binder-based coating λ ads = 0.36 W/m K 126 ; for zeolites, zeo-types, and silica gel, λ ads in the range 0.10–0.20 W/m K. 26,32,120 Restuccia et al 26 identified a binder-based coating with λ ads = 0.30 W/m K. λ ads values for condensed beds and specifically synthesized coatings were nearly two orders of magnitude higher than for binder-based coatings and loose grains/pellets. For loose grains, the values for convective heat transfer coefficients ( h ads ) are reported in the range of 70–120 W/m K, 133 but the most commonly used values are 10–50 W/m K. 133 For the other configurations, the convective heat transfer coefficients are greater than 1000 W/m K, such as, for directly synthesized SAPO-34 coatings on aluminum fibers, binder-based coating of silica gel, and consolidated 13X zeolite, the h ads are >1000 W/m K 125 for former, and up to 3000 W/m K 125,134 for the later ones, respectively. Such findings are helpful for improved interaction among the AHEx metal and adsorbent surface while consolidated beds or coatings are used rather than loose grains.…”
Section: Design and Operation Of Ahpsmentioning
confidence: 99%
“…This was discovered that when employing loose grains, the fin interval should be more than the adsorbent particle size, while the overall HEX length stays the same. Li et al 134 investigated silica gel in laminated bed designs. Hydroxyethylcellulose (HEC) was chosen among various binders, including bentonite, epoxy resin, and polyvinyl alcohol.…”
Section: Adsorbent Heat Exchanger (Ahex) Geometriesmentioning
confidence: 99%
“…It was found that in case of using loose grains, the fin spacing is recommended to be double adsorbent grain size while length of the whole HEX remains unchanged. Research on using silica gel in coated bed design was performed by Li A. et al [7,14]. Hydroxyethylcellulose (HEC) was selected from few different binders, e.g.…”
Section: Fin-tube Heat Exchangermentioning
confidence: 99%
“…We developed an advance silica gel with improved uptake by pore opening. We also developed silica gel-coated heat exchanger AD cycle that can achieve heat transfer coefficient twofold higher as compared to conventional packed bed AD cycle [106,107]. Silica gel has many advantages such as (i) easily available, (ii) lower cost as compared to all available adsorbent, (iii) more stable and reliable and (iv) easy to modify for required application [108][109][110][111].…”
Section: The Basic Adsorbent Cyclementioning
confidence: 99%